Effects of Almond Hull Inclusion on Growth Performance of Limit-Fed Growing Cattle - Z. M. Duncan; Z. L. DeBord; M. G. Pflughoeft; K. J. Suhr; W. R. Hollenbeck; F. K. Brazle; E. C. Titgemeyer; K. C. Olson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this experiment was to evaluate the effects of almond hull inclusion and almond hull processing on growth performance of limit-fed growing beef cattle during a 56-day growing period. Study Description:A total of 364 steers were assigned to one of four diets. The control diet contained (dry matter basis) 39.5% dry-rolled corn, 7.5% supplement, 40% wet-corn gluten feed, and 13% prairie hay. Almond hulls replaced prairie hay or prairie hay and dry-rolled corn and were fed at 13 and 26% of the diet, respectively. A subset of almond hulls was processed using a grinder mixer with no screen. Processed almond hulls replaced prairie hay and were fed at 13% of the diet. Diets were limit-fed for 56 days. The Bottom Line:These data were interpreted to suggest almond hulls can be utilized as an alternative to prairie hay in limit-fed growing beef cattle diets while maintaining or slightly improving growth performance.
Keywords: almond hulls; growing cattle; limit-feeding